The Role of Self-Support for Disability Persons as Essence for Peer Counseling - Sesya Dias Mumpuni; Ike Desi Florina; Sri Adi Nurhayat; Laelia Nurpratiwiningsih; Hijrah Eko Putro (Proceedings Series of Educational Studies, 2023)
It is important to address discrimination and stigma against disability in Tegal Regency society, which is the basis of this research. Members of the Inclusive Village Forum are residents who actively interact with people with disabilities. Families and communities do not always accept these conditions well. The Inclusive Village Forum was created to help people with disabilities regain confidence, want to develop and progress in their lives. These volunteers serve as the village's social capital to support people with disabilities. The purpose of this study is to find out what disabilities have in strengthening social capital through peer counseling of disabled volunteers in the Inclusive Village Forum. A total of 40 disability volunteers from the Inclusive Village Forum aged 15 to 55 years old were the respondents of this study. The data we obtained using a questionnaire was the respondents' perception of self-support. These results are social capital that will help respondents as a basis for self-understanding as peer counselors.